Respuesta :
Answer:
81m+27t
Step-by-step explanation:
We need to distribute the 9 to the terms inside the parentheses:
9(9m+3t)=9(9m)+9(3t)=81m+27t
Answer:
81m + 27t
Step-by-step explanation:
Explanation is attached below.
![Ver imagen kessmith4](https://us-static.z-dn.net/files/de8/abdef90b02ea581dce9647d50348cbce.png)
Answer:
81m+27t
Step-by-step explanation:
We need to distribute the 9 to the terms inside the parentheses:
9(9m+3t)=9(9m)+9(3t)=81m+27t
Answer:
81m + 27t
Step-by-step explanation:
Explanation is attached below.